UPAYA MENINGKATKAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI MELALUI MEDIA FILM KARTUN JUMBO - Nisa, Khoerunisa; Indrawati Noor Kamila; Husni (Hikamatzu | Journal of Multidisciplinary, 2025)
This study aims to analyze the effectiveness of the Jumbo cartoon film in improving early childhood social-emotional development at Kober Al-Hikmah, Cipaku District, Ciamis Regency. Initial observations revealed issues such as difficulty adapting, aggressive behavior, egocentrism, disobedience, and high temperament, which hindered children’s social interaction and emotional regulation. To address these issues, an engaging and educational medium was used, namely the Jumbo cartoon, which contains moral, social, and psychological values. This research employed a qualitative method with a descriptive approach. The subjects were 12 children, and data were collected through observation and document analysis using observation sheets as the main instrument. Data analysis was carried out using quantitative data analysis (SPSS). The results showed a significant improvement in children’s social-emotional development. Before the intervention, the average score was 23.67 (Beginning to Develop), and after the intervention, it increased to 30.3 (Developing as Expected). These findings demonstrate that the Jumbo cartoon effectively serves not only as entertainment but also as an educational medium that stimulates children’s empathy, cooperation, self-control, and confidence.